Trust No More? The Impact of Fraud Victimization on Generalized Trust in China - Xia, Yiwei (Victims & offenders, 2025)
This study explores the psychological consequence of fraud victimization on generalized trust in China, an area that has been less examined compared to the consequence of violent crime. Given that fraud specifically exploits victims’ trust, this research aims to determine whether fraud victimization leads to a decline in generalized trust and the duration of this effect. Using data from the China Family Panel Studies (CFPS), a nationally representative longitudinal survey from 2012 to 2020, the study applies logistic regression models to assess the short- and long-term effects of fraud on generalized trust, controlling for various demographic and socio-economic factors. The findings reveal that fraud victimization significantly reduces generalized trust for up to two years, after which trust levels tend to recover, suggesting that the impact of fraud on trust, though significant, may be temporary. This research contributes to a broader understanding of how property crimes, particularly fraud, affect societal trust, highlighting that while fraud can erode trust, recovery is possible. Future studies should further investigate these dynamics, particularly the role of social and reinforcement learning in trust recovery, and employ more frequent data collection to better capture the timing of trust restoration.